The impact of internet use on residents’ happiness in China - Sun, Yongqiang; Gao, Jing; Zhang, Xiaolin; Cheng, Yaoxing (Frontiers in Public Health, 2023)
Using data from the 2018 Chinese General Social Survey (CGSS), this study investigates the impact of Internet use on residents’ happiness. Empirical results show that Internet use significantly enhances residents’ happiness. Considering the possible endogeneity problem, a two-stage tool variable estimation is carried out with ownership of a mobile phone as the tool variable. After overcoming the endogenous problem and conducting a series of robustness tests, the conclusion is still valid. The action mechanism finds that social interaction frequency and socioeconomic status (SES) play significant mediating effects in the process of Internet use affecting happiness. Specifically, Internet use significantly increases the social interaction frequency of residents and enhances their SES. The improvement of social interaction frequency and SES will significantly increase residents’ happiness. Therefore, this paper gives policy recommendations from the perspectives of regulating and deepening Internet use, increasing the frequency of communication among residents, and improving their SES to better enhance their happiness.